The spacial concentration of the multinational corporation Google in years 2006–2010 - Boguś, Marta (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2012)
The predominant role played by multinational corporations comes as a result of the globalization process. In the modern era of knowledge, we observe intensive development of high technology industries, mainly computer science. The IT corporations are looking for the effective locations for their offices. This article presents an analysis of the changes in the spatial structure of the economic potential of the Google corporation in years 2006-2010.Google was established in 1998. Since then, it has developed rapidly and become a leader in computing and Internet search. 73 departments of the corporation are located in 43 countries, usually in the capitals of these countries or in rather large cities, which are associated with major public markets. The leading actors are 26 departments located in Europe and 24 departments located in the North America. The headquarters of Google is located in Mountain View, California. Individual countries have varying degree of presence of Google offices, the greatest number being located in the United States - 20, whilst 3 are located in Poland: in Warsaw, Cracow and Wroclaw.The economic potential of Google has been concentrated in three areas: the United States, the United Kingdom and other countries. In years 2006-2010, the value of profits in each area increased; the most dynamic growth was noticed in other countries. In years 2007-2010, the value of assets had the same growth tendencies. Judging by its economic potential, it is said that Google is developing rapidly, especially outside the United States. It is caused by the fact that the American market is already controlled and new markets all over the world are searched for and explored.